(untitled) (gjstudies, 2022)
This research introduces a novel, cross-disciplinary framework for environmentalcost accounting (ECA) that integrates principles from ecological economics, complexsystems theory, and information entropy to address the persistent shortcomings incorporate environmental performance measurement. Traditional ECA methods havelargely failed to capture the full spectrum of environmental externalities, often relying on linear, reductionist models ill-suited to the non-linear, interconnected natureof ecological impacts. Our methodology, termed the Entropic Environmental CostAccounting (EECA) framework, departs from conventional practice by conceptualizing corporate operations as thermodynamic systems interacting with ecological networks. We employ a hybrid technique combining life cycle assessment (LCA) data withinformation-theoretic measures of ecological disruption, specifically applying KullbackLeibler divergence to quantify the ’informational distance’ between pre- and postindustrial ecosystem states. This allows for the monetization of entropy changes withinaffected environmental systems, translating diffuse ecological degradation into quantifiable financial liabilities. A core innovation is the ’Ecological Carrying CapacityDebt’ metric, a dynamic, time-dependent valuation of a corporation’s cumulative drawon regenerative ecosystem services beyond sustainable thresholds. We test the EECAframework through a longitudinal, multi-case study analysis of four corporations in theextractive and manufacturing sectors, utilizing a proprietary dataset of operational andenvironmental data from 1995 to 2004. Our results demonstrate that the EECA framework identifies and quantifies significant, previously uncosted environmental liabilities,averaging 18-34